1998
DOI: 10.1046/j.1471-4159.1998.71031280.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Group III Metabotropic Glutamate Receptors in Excitotoxin‐Induced Cerebellar Granule Cell Death

Abstract: Abstract:The neuronal effects of the metabotropic glutamate receptor agonist (1 S,3R)-aminocyclopentane-1 ,3-dicarboxylic acid have been studied in cultured rat cerebellar granule cells, and compared with those of the endogenous excitotoxin glutamate, and the dietary excitotoxin /3-N-methylamino-L-alanine. Glutamate,~3-N-methylamino-L-alanine, and (1 S ,3R) -aminocyclopentane-1 ,3-dicarboxylic acid all caused concentration-dependent cerebellar granule cell death over a 24-h exposure period. The metabotropic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A similar drug action was also observed in a minority of DAergic neurons. BMAA has been previously reported to potently activate mGluRs in hippocampal, striatal, and cerebellar neurons (Copani et al, 1990(Copani et al, , 1991Manzoni et al, 1991;Staton and Bristow, 1998;Lobner et al, 2007). Alternatively, it predominantly activates NMDA receptors in cortical neurons (Weiss et al, 1989;Lobner et al, 2007) and AMPA/kainate receptors in spinal motoneurons (Rao et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar drug action was also observed in a minority of DAergic neurons. BMAA has been previously reported to potently activate mGluRs in hippocampal, striatal, and cerebellar neurons (Copani et al, 1990(Copani et al, , 1991Manzoni et al, 1991;Staton and Bristow, 1998;Lobner et al, 2007). Alternatively, it predominantly activates NMDA receptors in cortical neurons (Weiss et al, 1989;Lobner et al, 2007) and AMPA/kainate receptors in spinal motoneurons (Rao et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that BMAA activates different types of glutamate receptors in diverse brain areas (Spencer et al, 1987;Copani et al, 1990Copani et al, , 1991Allen et al, 1993;Pai et al, 1993;Staton and Bristow, 1998;Rao et al, 2006;Lobner et al, 2007). To this regard, we aimed to explore its effect onto the "secondary" cells of the SNpc, presumably GABAergic neurons ( Fig.…”
Section: Bmaa Activates Ampa Receptors In Gabaergic Neurons Of the Snpcmentioning
confidence: 99%
“…The development of such antagonists as clinically useful neuroprotectants has been limited by the complex nature of glutamate receptors. Depending on the model system assessed, roles for each of several subtypes of glutamate receptors have been proposed in mediating glutamate excitotoxicity (Olney et al, 1989; Buchan et al, 1991; Kaku et al, 1991; Albers et al, 1992; Le Peillet et al, 1992; Gill, 1994; Buisson and Choi, 1995; Mukhin et al, 1996; Staton and Bristow, 1998). Lack of specificity of some glutamate receptor antagonists has also limited clinical utility, leading to unwanted side effects, such as psychosis (Carter, 1994; Muir and Lees, 1995; Turski et al, 1998).…”
mentioning
confidence: 99%